Meta-narrative is a method of writing narrative within narrative and its practice in Abdullah Saraj's short story Mam Wasoo - رسول, م. م. گزنگ حسن رسول (Sulaimani Journal for Humanities, 2025)
Meta-narrative is a genre of literary narrative that goes beyond ordinary and traditional narrative. It emphasizes the structure of its own narrative and consciously draws the reader's attention to the aspects of the narrative through excitement and questioning it is outside itself. Therefore, the task of meta-narrative is to investigate its characteristics and objectives that affect readers’ participation, from the narrator to the narrative, combining several layers of narrative such as stories within the main story and creating a complex narrative structure. This abstraction determines the dynamic correspondences between (Author, Text, Reader) in which it disintegrates the layers of meaning and the extremities of the bonds between reality and imagination. In meta-narrative, the reader is confronted with a narrative that does not only find itself in reading the text, but also investigates the narrative process itself to create another meaning in the text through the expression of creative energy. To put it another way, the recipient participates in the construction of the text through the correspondence between the author and the reader. He objectifies these processes involved in the creation of the literary subject. This type of writing a novel affected all spheres of life with the advent of postmodernism. It was a step from the realistic novel towards experiencing modernity and postmodernism.
Keywords: Metanarrative; imagination; self centeredness; story within story; Abdullah Saraj